2016
DOI: 10.1002/ecs2.1438
|View full text |Cite
|
Sign up to set email alerts
|

Preserving prairies: understanding temporal and spatial patterns of invasive annual bromes in the Northern Great Plains

Abstract: Abstract. Two Eurasian invasive annual brome grasses, cheatgrass (Bromus tectorum) and Japanese brome (Bromus japonicus), are well known for their impact in steppe ecosystems of the western United States where these grasses have altered fire regimes, reduced native plant diversity and abundance, and degraded wildlife habitat. Annual bromes are also abundant in the grasslands of the Northern Great Plains (NGP), but their impact and ecology are not as well studied. It is unclear whether the lessons learned from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 58 publications
(80 reference statements)
2
19
0
Order By: Relevance
“…In the absence of Amorpha , the nonnative component of plant cover doubled to tripled at N addition levels within the range of current deposition, and this increase featured invasive annual Bromus grass species known to be problematic, and in some places increasing in prominence, in NGP grasslands (Ashton et al. ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the absence of Amorpha , the nonnative component of plant cover doubled to tripled at N addition levels within the range of current deposition, and this increase featured invasive annual Bromus grass species known to be problematic, and in some places increasing in prominence, in NGP grasslands (Ashton et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Nonnative species abundance increased in only one site (Hilltop), but this increase was one of the most striking and consistent responses to N addition in our study, serving as a basis for one critical load estimate for this site. In the absence of Amorpha, the nonnative component of plant cover doubled to tripled at N addition levels within the range of current deposition, and this increase featured invasive annual Bromus grass species known to be problematic, and in some places increasing in prominence, in NGP grasslands (Ashton et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Many patches of grassland that remain are severely invaded (Wilsey et al ), with cool‐season perennial grasses Bromus inermis and Poa pratensis being dominant invaders (Cully et al ; DeKeyser et al ). In fact, more than 80% of the annual production in some grasslands come from B. inermis and P. pratensis (DeKeyser et al ; Ashton et al ). Restoration and management to control invasive cool‐season grasses in these grasslands are often met with limited success (reviewed in Ellis‐Felege et al ) and cool‐season invasive grasses often persist after intensive initial restoration efforts (Larson et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Instead of a search for generality, the place-based approach steeps itself directly in the messy, idiosyncratic details of real ecosystems. Ashton et al (2016) replicated vegetation surveys among prairie parks and found previously undescribed cyclical variation in invasive brome grass dynamics that will greatly benefit park weed management. For example, Brown et al (2016) applied a common protocol to coral reefs in four parks that revealed among-park variation in stressors and subsequent management recommendations.…”
Section: Special Feature Highlightsmentioning
confidence: 60%